2018
DOI: 10.1007/s13365-018-0640-6
|View full text |Cite
|
Sign up to set email alerts
|

Motor function declines over time in human immunodeficiency virus and is associated with cerebrovascular disease, while HIV-associated neurocognitive disorder remains stable

Abstract: HIV-associated neurocognitive disorders (HAND) remain prevalent in the combined antiretroviral therapy (CART) era, especially the milder forms. Despite these milder phenotypes, we have shown that motor abnormalities persist and have quantified them with the HIV Dementia Motor Scale (HDMS). Our objectives were to replicate, in an independent sample, our prior findings that the HDMS is associated with cognitive impairment in HIV, while adding consideration of age-associated comorbidities such as cerebrovascular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 25 publications
3
29
1
Order By: Relevance
“…Our findings support this suggestion, and are consistent with prior studies in HIV demonstrating an association between neuropsychiatric abnormality and frailty status [9,10]. Although the underlying mechanism of this association cannot be determined in our study, prior studies have demonstrated an association between motor abnormality (and with particular relevance to frailty, abnormal gait) and cognitive impairment, both in PLWH and HIV-negative populations [19][20][21]. In turn, motor and cognitive abnormalities may be correlated with cerebral white matter disease on neuroimaging [22][23][24].…”
Section: Discussionsupporting
confidence: 92%
“…Our findings support this suggestion, and are consistent with prior studies in HIV demonstrating an association between neuropsychiatric abnormality and frailty status [9,10]. Although the underlying mechanism of this association cannot be determined in our study, prior studies have demonstrated an association between motor abnormality (and with particular relevance to frailty, abnormal gait) and cognitive impairment, both in PLWH and HIV-negative populations [19][20][21]. In turn, motor and cognitive abnormalities may be correlated with cerebral white matter disease on neuroimaging [22][23][24].…”
Section: Discussionsupporting
confidence: 92%
“…These results suggest that gross upper limb motor impairments may be an overlooked effect of HIV and that the BBT can be used to identify these impairments as an alternative to the GP. This approach could be useful when examining patients with both HIV and stroke in particular, when motor impairments may be more prevalent [44].…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that gross upper limb motor impairments may be an overlooked effect of chronic HIV and that the BBT can be used to identify these impairments as an alternative to the GP. This approach could be useful when examining patients with both HIV and stroke in particular, when motor impairments may be more prevalent [44].…”
Section: A Gross Motor Impairments Are Prevalent In Plwhmentioning
confidence: 99%